Cell-based Hyper-interleukin 6 or Hyper-interleukin 11 secreting vaccines combined with low dose cyclophosphamide in an orthotopic murine prostate cancer model - Mackiewicz, Jacek; Kotlarski, Marek; Dondajewska, Ewelina; Nowicka-Kotlarska, Anita; Krokowicz, Łukasz; Kazimierczak, Urszula (Contemporary Oncology/Współczesna Onkologia, 2015)
Background: Cell based vaccines encoding Hyper-IL-6 (H6) and Hyper IL-11 (H11) present high activity in murine melanoma and renal cancer model. We evaluated the efficacy of cellular vaccines modified with H6 or H11 combined with cyclophosphamide in orthotopic murine prostate cancer model. Material and methods: TRAMP cells were transduced with H6 and H11 cDNA (TRAMP-H6 and TRAMP-H11). An orthotopic TRAMP model based on the implantation of TRAMP cells into the dorsolateral lobe of the prostate of C57BL6/J mice was employed. The efficacy of TRAMP-H6 and TRAMP-H11 vaccines evaluated in the therapeutic setting was compared with the TRAMP cells modified with a mock transduced E1-deleted adenoviral vector (TRAMP-AdV) and non-modified irradiated TRAMP cells (TRAMP IRR) in relation to naive (non-immunized) mice. In the next experimental groups mice vaccinated with TRAMP-H6 and TRAMP-H11 received cyclophosphamide (CY). Detection of immune cells in the spleen in mice receiving vaccines combined with CY was evaluated. Results: Modification of TRAMP cells with H6 increased the efficacy of TRAMP-based whole-cell vaccine. The highest response rate was observed in mice receiving TRAMP-H6 alone and combined with CY. Vaccination with TRAMP-H6 alone and combined with CY and TRAMP H11 combined with CY extended median OS of mice bearing orthotopic TRAMP tumors in therapeutic setting. Low dose CY administered alone demonstrated some antitumor activity in employed model. TRAMP-H6 or TRAMP-H11 combined with CY strongly augmented generation of CD8+, CD4+ T lymphocytes and memory T cells. Immunization with TRAMP combined with or without CY suppressed generation of T regulatory cells. Conslusions : Prostate cancer vaccines modified with H6 or H11 induce prostate tumour regression and increase mice survival by stimulating the immune system. Cyclophosphamide added to modified TRAMP vaccines demonstrated clinical benefit of treated mice and enhanced anti-tumour immune response.